(untitled) (International Journal of Engineering and Computer Science, 2024)
The article aims to present one aspect of the impact of the imposition of pandemic restrictions on the quality of education. The results of the evaluation of students at the New Bulgarian University (NBU), Bulgaria, Department of Informatics before, during and after the pandemic were analyzed. All students are in the upper year of their studies in bachelor program. Assessment results in 3 courses are presented: „Computer periphery” (5th semester), “Digital video formats” (7th semester), “Fundamentals of multimedia presentation” (6th semester).